The Role of PNM Mekaar Syariah’s Financial Education in Enhancing the Financial Literacy of Elementary School Teachers in Sungai Aur Village, Jambi - Wahyuti; M. Arif Musthofa; Sayida Khoiratun Nisak (MODELING: Jurnal Program Studi PGMI, 2026)
Financial literacy is an important determinant of individual financial well-being, particularly among elementary school teachers who are expected to make sound financial decisions in managing personal and professional financial responsibilities. However, limited access to structured financial education remains a challenge for teachers in rural communities, potentially affecting their ability to manage finances, make responsible borrowing decisions, develop saving habits, and mitigate financial risks. This study examines the contribution of financial education provided by PNM Mekaar Syariah to strengthening the financial literacy of elementary school teachers at SD Negeri 234/IX Sungai Aur, Jambi, Indonesia. The study focuses on how sharia-oriented financial education influences teachers’ financial knowledge, attitudes, and management practices. A qualitative research design was employed to explore teachers’ experiences, perceptions, and interpretations of the financial education received and its relevance to everyday financial decision-making. Data were collected through in-depth interviews, observations, and document analysis and analyzed thematically. The findings indicate that financial education provided by PNM Mekaar Syariah contributes to improved financial literacy, particularly in financial planning, responsible borrowing, saving practices, and prudent financial decision-making. The integration of sharia principles also promotes greater awareness of responsible financial behavior, including financial sustainability, avoidance of excessive debt, and disciplined financial planning. The study concludes that contextually relevant, sharia-based financial education can support financial inclusion and sustainable financial behavior among teachers in rural communities. These findings highlight the potential of community-based Islamic financial institutions to strengthen financial capabilities and financial resilience at the grassroots level.